Craving for chocolate buns? / Ng Set Foong and Aishah Mahat - Ng, Set Foong; Mahat, Aishah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Commercial sweet buns are selected by consumers based on several factors such as its convenience, shelf life and taste. The commercial sweet buns are usually filled with different types of paste. The ingredients and nutrient contents of the commercial sweet buns are usually well known to other people through the printed information on the packaging. However, detailed and scientific comparison on the nutritional composition of the buns are seldom carried out. In this study, the nutritional composition of five types of different flavours of commercial sweet buns such as chocolate, kaya, red bean, coconut and potato bun is analysed with a mathematical technique named as Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The analysis of this study has identified the type of bun that has the most nutrient contents which are good for health and has the least of non-benefit nutrient contents that are bad for health. The result could be served as a reference for people who is conscious on nutrition and health.